Moderation, Character, and Pesantren Traditions: Actualization of KH. Hasyim Asy’ari’s Ideas in Islamic Religious Education - Jasminto Jasminto; Siti Rofi’ah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to explore the integration of the thoughts of Hadratussyaikh KH. Muhammad Hasyim Asy’ari into the curriculum of the Islamic Religious Education (PAI) Study Program at Hasyim Asy’ari University, Tebuireng. Using a qualitative approach through in-depth interviews, observation, and document analysis, the research highlights the actualisation of pesantren values inherited from KH. Hasyim Asy’ari within the context of contemporary Islamic higher education. The main focus is on three core pillars: religious moderation, character development, and the preservation of pesantren traditions, which form the foundation of a sustainable Islamic education vision. The findings indicate that Hadratussyaikh’s ideas—such as the importance of manners (adab), sincerity, accessible scholarship, and a moderate religious spirit—have been integrated into both the curriculum and learning practices. These values not only shape a religious and inclusive academic atmosphere but also strengthen students' identities as agents of change rooted in traditional Islamic scholarship. This integration is reflected in course content and teaching methods, as well as students' religious and social activities, all directed toward forming academically excellent individuals with strong morals and adaptability to contemporary challenges. Thus, this study affirms that KH. Hasyim Asy’ari’s ideas are both relevant and strategic in formulating a model of Islamic religious education that bridges tradition and modernity. The results are expected to serve as a reference for the development of contextual and transformative pesantren-based curricula